2017
DOI: 10.1038/srep40991
|View full text |Cite
|
Sign up to set email alerts
|

Design of an expression system to enhance MBP-mediated crystallization

Abstract: Crystallization chaperones have been used to facilitate the crystallization of challenging proteins. Even though the maltose-binding protein (MBP) is one of the most commonly used crystallization chaperones, the design of optimal expression constructs for crystallization of MBP fusion proteins remains a challenge. To increase the success rate of MBP-facilitated crystallization, a series of expression vectors have been designed with either a short flexible linker or a set of rigid helical linkers. Seven death d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 58 publications
(79 reference statements)
0
30
0
Order By: Relevance
“…To overcome the aggregation of DR3 DD due to its high hydrophobicity, we used an N‐terminal maltose‐binding protein (MBP) as a crystallization tag. This technique has been used successfully in the structural determination of several DD folds . To increase the success rate of MBP‐facilitated crystallization, we used a series of expression vectors with a set of rigid helical linkers and harvested both human and mouse MBP–DR3 DD crystal structures with one‐amino‐acid difference in the linkers between MBP tag and DR3 DD (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the aggregation of DR3 DD due to its high hydrophobicity, we used an N‐terminal maltose‐binding protein (MBP) as a crystallization tag. This technique has been used successfully in the structural determination of several DD folds . To increase the success rate of MBP‐facilitated crystallization, we used a series of expression vectors with a set of rigid helical linkers and harvested both human and mouse MBP–DR3 DD crystal structures with one‐amino‐acid difference in the linkers between MBP tag and DR3 DD (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to crystallize CAMP factor with a maltose-binding protein (MBP) tag, the CAMP-coding region was re-cloned into pET-30a vector with a non-cleavable N-terminal MBP tag. The MBP tag was designed with the following surface entropy-reducing mutations to enhance crystallization: D82A/K83A/E172A/N173A/K239A (Moon et al, 2010;Jin, Perry et al, 2013;Jin et al, 2017). A series of fusion constructs was created in which the N-terminal residue of the CAMP-factor reading frame was varied systematically in two-residue increments from Ala29 to Met50 in order to increase the chance of fusion-protein crystallization.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…Inspired by the successful use of MBP as a crystallization chaperone for crystallizing challenging targets by our group and several others (Potter et al, 2008;Moon et al, 2010;Jin et al, 2017), we decided to try the MBP-fusion tag to solve the phase problem of CAMP crystals. The use of a crystallization tag to aid target-protein crystallization usually requires a reasonable structural model.…”
Section: Mbp Fusion Tag-aided Crystallizationmentioning
confidence: 99%
“…One approach to stabilize flexible proteins has been described by Moon and coworkers and utilizes maltosebinding protein (MBP) with surface-entropy reduction (SER) mutations as an N-terminal carrier protein to enhance protein crystallization (Moon et al, 2010). MBP has been reported to enhance the solubility of proteins when expressed as an N-terminal fusion in Escherichia coli (Waugh, 2016;Jin et al, 2017) and mammalian expression systems (Reuten et al, 2016;Bokhove et al, 2016), but to date this has not been reported for insect-cell expression systems. We describe the expression of the FXIIa protease domain as a secreted MBP fusion using DES, which facilitated the crystal structure determination of MBP-FXIIa His in the active conformation in complex with the peptidomimetic inhibitor d-Phe-Pro-Arg chloromethyl ketone (PPACK).…”
Section: Introductionmentioning
confidence: 99%